A new Markov chain approach for the economic statistical design of the VSS T2 control chart. Issue 1 (2nd January 2019) - Seif, Asghar
ABSTRACT: An economic statistical design model for a T 2 chart which uses a variable sample size (VSS) feature is developed in this article. This study mainly differs from the others conducted in the field. In that a new approach is offered to achieve closed form of some statistical criteria. In other words, the proposed formulas can be considered as a better alternative approach in designing the VSS control charts in terms of simplicity and yet providing the users with better optimal solutions.